A STUDY TO ASSESS THE USE AND COMPLETION OF THE ELECTRONIC KEY INFORMATION SUMMARY (KIS) AT THE POINT OF HOSPITAL ADMISSION FOR PATIENTS AT RISK OF DETERIORATION OR DYING. Issue 1 (1st March 2015) - Hall, CC; Spiller, JA
Abstract : Introduction: The electronic Key Information Summary (KIS) is an evolution of the Emergency Care Summary. The KIS contains vital patient information, is accessible to unscheduled/ emergency care services and more recently in secondary care. A KIS is completed by GPs for any patient with complex care needs. Information ranges from a "special note" to a comprehensive electronic Palliative Care Summary. Little is known however about the usefulness and perspectives of hospital clinicians regarding the KIS. Aim(s) and method(s): Aims: To identify acute medical admissions with a KIS and analyse KIS quality. To identify those at risk of deterioration/ dying (using SPICT™ tool). To ascertain levels of clinician KIS awareness/ access, views on usefulness and suggested improvements. Methods: Retrospective case note analysis/ semi-structured interviews. Results: 24% of all patients had a KIS. Of patients at risk of deterioration or dying, 53% had a KIS. KIS quality was variable. Access to ECS medications (which now includes an 'abbreviated' KIS) was high (96%) but only 19% of clinicians had viewed their patient's KIS. Access to a 'full' KIS (including Palliative Care fields) was only 4%. 75% of clinicians found the KIS a useful tool. Conclusion(s): KIS are present for almost 1/4 of medical admissions to secondary care and are deemed useful by the majority of admitting clinicians. Patients at risk of deterioration or dying are more likely to have a KIS, but KIS are not routinely viewed by admitting clinicians. Education regarding the KIS/SPICT™ in hospitals and prompting on admission may improve complex (including palliative) patient management.